2018
DOI: 10.1016/j.joms.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Does Surgical Fragmentation of Odontogenic Keratocystic Capsule Interfere With the Recurrence Rate?

Abstract: Fragmentation of the cystic capsule does not play an important role in the rate of OKC recurrence. The rate of recurrence can be modified by using additional strategies such as cryotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been shown that fragmentation of the cystic capsule during surgical excision does not affect the recurrence rate of OKCs. [ 16 ] Incomplete removal of the cystic lesion allows new cyst formation or epithelial islands in the wall of the original cyst remain in the surrounding bone or soft tissue. New OKCs can also develop from the basal layer of the oral epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that fragmentation of the cystic capsule during surgical excision does not affect the recurrence rate of OKCs. [ 16 ] Incomplete removal of the cystic lesion allows new cyst formation or epithelial islands in the wall of the original cyst remain in the surrounding bone or soft tissue. New OKCs can also develop from the basal layer of the oral epithelium.…”
Section: Discussionmentioning
confidence: 99%